PENERAPAN MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PPKN KELAS IV - Sri Wahyuni; Munirah; Karmila Iskandar (Al-mujahidah, 2026)
This study aims to improve student learning outcomes, implementation and challenges in implementing the Project Based Learning model in the PPKN subject for fourth-grade students at SDN 21 Limboto. This type of research is classroom action research. The subjects of this study were 24 fourth-grade students at SDN 21 Limboto. The data analysis techniques used in this study were test result analysis and observation result analysis. Based on the results of the study, it can be concluded that PPKN learning on rights and obligations using the Project Based Learning model can improve the learning outcomes of fourth-grade students at SDN 21 Limboto. This is indicated by the improvement in student learning outcomes in cycles I and II. In cycle I, 17 students were categorized as achieving the Minimum Completion (KKM) with a percentage of 70% and in cycle II, 24 students were categorized as achieving the KKM value with a percentage of 96%. So the KKM increased by 26%. This is because in cycle II, students have begun to improve in the learning process, most students have been able to understand the material. So, student learning outcomes in cycle II have reached the KKM value or the specified performance indicators. Thus, the hypothesis in this study is that using the Project Based Learning model can improve the learning outcomes of fourth grade students at SDN 21 Limboto.